Analysis Empowerment Disabled Community Melalui Industri Kecil Menengah (Studi Kasus Di Desa Sentul Kec. Purwodadi Kab. Pasuruan) - Mir'ah, Lailatul; Said, M. Mas’ud; Musa, Ali Masykur (BRILIANT: Jurnal Riset dan Konseptual, 2024)
Empowering people with disabilities is very important because they often experience discrimination and find it difficult to gain access to public services, education, health and employment. This results in limitations in developing their potential. This research focuses on efforts to empower the disabled community in Sentul Village, especially in the Kupu Sutera Small and Medium Industry. The aim of this research is to analyze the potential of the disabled community, describe efforts to empower them in the Kupu Sutera Small and Medium Industry, and assess the impact. The research method used is qualitative with a descriptive approach. The research results show that Kupu Sutera has trained 72 people with disabilities, including 39 Pasuruan residents and 33 Malang residents. Through this training, people with disabilities learn to cultivate silkworms, separate threads from cocoons, spin, batik, weave, dye silk cloth, sew and make accessories. This empowerment has a positive impact, helping people with disabilities feel confident and able to compete with the general public.